Teaching for preparedness: Indonesian physical education teachers’ roles in the disaster education - Saryono, Saryono; Nurkamto, Joko; Hidayatullah, M. Furqon; Komarudin, Komarudin (Jurnal Cakrawala Pendidikan, 2026)
Indonesia’s high vulnerability to natural disasters has placed increasing importance on the Disaster Risk Reduction (DRR) education. Much of the existing literature emphasizes disaster education in scientific school subjects, but physical education (PE) remains underexplored yet promising. This qualitative study investigated the perceptions of PE teachers in disaster-prone regions of Central Java, Indonesia, and the implementation of disaster education in their teaching practices. Drawing on semi-structured interviews with 14 junior high school PE teachers, thematic analysis revealed three central themes: 1) the contextual realities shaping teachers’ experiences, 2) the perceived value of PE as a vehicle for disaster education, and 3) the creative pedagogical strategies in disaster education. Despite limited curriculum support, teachers integrated disaster education through warming-up routines, simulation games, and fitness activities to develop agility, coordination, and leadership among students. The findings highlight PE’s applied and experiential aspects as well as its potential for interdisciplinary collaboration. However, the study also exposes systemic barriers, such as centralized policy constraints and lack of institutional support. To enhance disaster preparedness in schools, the study advocates for policy reforms that integrate disaster education into the PE curriculum and promote localized and context-sensitive practices. These efforts can contribute meaningfully to student safety, community resilience, and holistic educational development.